Determination of acid dissociation constants and reaction kinetics of dimethylamine-based PPCPs with O3, NaClO, ClO2 and KMnO4. Issue 6 (12th May 2019) - Wang, Xiaofeng; Zhou, Beihai; Shao, Xia
Abstract: Dimethylamine-based pharmaceutical personal care products (DMA-based PPCPs) are a group of N -nitrosodimethylamine (NDMA) precursors. The acid dissociation constant (pKa) values of four DMA-based PPCPs were determined by potentiometric titration over the pH range of 3–11. The pKa values of ranitidine, nizatidine, doxylamine and carbinoxamine corresponding to the DMA moiety were 8.4, 6.8, 9.4 and 9.1, respectively. Competition reaction kinetics and pseudo-first-order reaction kinetics were used to determine the reaction rate constant ( k ) of the DMA-based PPCPs with O3, NaClO, ClO2 and KMnO4 . Comparing the degradation rate constants of the four DMA-based PPCPs, the results of ClO2 oxidation were close, and for the other three oxidants, the order was k ranitidine ≈ k nizatidine > k doxylamine ≈ k carbinoxamine . Comparing the reaction rate of the four oxidants, for ranitidine and nizatidine, the order was k NaClO > k O3 > k KMnO4 > k ClO2, and for doxylamine and carbinoxamine, the order was k O3 > k NaClO > k ClO2 > k KMnO4 .